Jawetz, Melnick & Adelberg's medical microbiology - Brooks, George F.; Carroll, Karen C.; Butel, Janet S.; Morse, Stephen A.; Mietzner, Timothy A. (McGraw-Hill Medical, 2013)
Jawetz, Melnick & Adelberg's Medical Microbiology, 26e introduces you to basic clinical microbiology through the fields of bacteriology, virology, mycology, and parasitology, giving you a thorough yet understandable review of the discipline.